2021
DOI: 10.1142/s0218348x21502352
|View full text |Cite
|
Sign up to set email alerts
|

Analog Implementation of Fractional-Order Electric Elements Using Caputo–fabrizio and Atangana–baleanu Definitions

Abstract: This study employs the Caputo–Fabrizio and Atangana–Baleanu fractional derivatives to determine the impedance and admittance model of fractional capacitor and inductor. The analog implementation circuits are proposed aiming at fractional-order electric elements based on these two derivatives, which can be widely used in a variety of electrical systems using new fractional operators. Constant phase capacitor and inductor are approximated by the Oustaloup algorithm and the recursive net-grid-type analog circuit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Fitting the model using real data and parameter estimation in the fractional order models is an integral part in the disease modeling. Therefore, in this study we use both the least squares and Nelder mead algorithm methods [7] to fit and estimate the parameters ( h , θ h , α h ) of the proposed model (2.1). The real data used in this study are weekly reported cases in Zimbabwe as presented in Table 3, and the commutative new infections predicted by the model (2.1) is obtained using the equation (3.13):…”
Section: Parameter Estimations Using Weekly Reports Of Malaria Cases ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fitting the model using real data and parameter estimation in the fractional order models is an integral part in the disease modeling. Therefore, in this study we use both the least squares and Nelder mead algorithm methods [7] to fit and estimate the parameters ( h , θ h , α h ) of the proposed model (2.1). The real data used in this study are weekly reported cases in Zimbabwe as presented in Table 3, and the commutative new infections predicted by the model (2.1) is obtained using the equation (3.13):…”
Section: Parameter Estimations Using Weekly Reports Of Malaria Cases ...mentioning
confidence: 99%
“…Nevertheless, the complexities in the parasite's life cycle, coupled with the highly complex social and environmental interactions, and movement of people between endemic and non-endemic areas continue to promote morbidity and mortality from malaria. Although combined global efforts are underway to develop a malaria vaccine [7], [8], [9], [10], there is currently no perfect vaccine against the disease. As such, concerted attempts are still being made to understand malaria disease dynamics and effective control measures.…”
Section: Introductionmentioning
confidence: 99%
“…the nonsingular kernels (Atangana and Alkahtani, 2016, 2015; Das, 2020; Gómez-Aguilar et al , 2016, 2017; Gómez‐Aguilar, 2018; Liao et al , 2021, 2022a, 2022b; Sheikh et al , 2020). Therefore, the nonlocal fractal calculus is inapplicable to those circuits whose memory effects are described by nonsingular kernels (Atangana and Alkahtani, 2015; Gómez‐Aguilar et al , 2016, 2017; Gómez‐Aguilar, 2018; Liao et al , 2021, 2022b, 2022a; Sheikh et al , 2020). In addition, according to its basis fractional derivatives, the nonlocal fractal calculus-based dynamical equation of any fractal electrical circuit with memory effect can be given in either Riemann–Liouville sense or Caputo sense, where the latter has been chosen (Banchuin, 2022c; Ali et al , 2023; Banchuin, 2023) due to its simpler initial condition handling methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Note also that such Atangana-Baleanu fractional derivative has been applied, cited, and studied in many research areas ranged from electrical engineering to epidemiology. 27,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] In particular, we choose the Atangana-Baleanu fractional derivative in Liouville-Caputo sense rather than the derivative in Riemann-Liouville sense. This is because the former takes the initial condition into its Laplace transformation, 30,33 and we solve the fractional-order memristor's state equation of by means of the Laplace transformation-based methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Between two well‐known nonsingular kernel fractional derivatives, i.e., the Caputo‐Fabrizio fractional derivative 29 and the Atangana‐Baleanu fractional derivative 30 ; we choose the latter as it is a generalization of the former and also nonlocal. Note also that such Atangana‐Baleanu fractional derivative has been applied, cited, and studied in many research areas ranged from electrical engineering to epidemiology 27,31–44 . In particular, we choose the Atangana‐Baleanu fractional derivative in Liouville‐Caputo sense rather than the derivative in Riemann‐Liouville sense.…”
Section: Introductionmentioning
confidence: 99%